Comparative analysis of the age estimates for greenland halibut Reinhardtius hippoglossoides matsuurae in the North-West Pacific based on different methodological approaches - O. Z. Badaev; I. S. Chernienko; S. L. Ovsyannikova (Известия ТИНРО)
Significant decline in abundance of greenland halibut Reinhardtius hippoglossoides matsuurae in the North-West Pacific is one of the reasons for development the methods of this species age determination using different age-recording structures. The study is based on recommendations of the Northwest Atlantic Fisheries Organization (NAFO) and International Council for the Exploration of the Sea (ICES). Underestimation of age is found for the records on scales or whole otoliths, compared to records on the otolith slices through the tubercle. An exploitation strategy based on improper age determination can have a negative impact on the state of the greenland halibut stock, in combination with natural causes, or even be a major reason of this species depression.